Factors associated with persistent hypertension after puerperium among women with pre-eclampsia/eclampsia in Mulago hospital, Uganda - Kaye Dan K; Nakalembe Miriam; Ndayambagye Emmanuel B (BMC, 2010)
Abstract Background Women with severe pre-eclampsia/eclampsia are at risk of developing chronic hypertension in future. Chronic hypertension may manifest initially as persistent hypertension at the end of the puerperium. The objective was to determine the incidence and maternal biochemical, hematological and socio-demographic risk factors for persistent hypertension in patients with pre-eclampsia/eclampsia. Methods This was a prospective cohort study conducted from November 2008 to May 2009 at Mulago hospital labor ward and postnatal clinic. Participants were 200 women managed for pre-eclampsia/eclampsia and followed up to the end of the puerperium. Data was collected through using pre-coded interviewer-administered questionnaires, checking medical records and laboratory investigations. STATA (release 9) software was used for data analysis. At bivariate analysis, the relative risk of persistent hypertension was estimated at the 95% confidence level. Using multivariate logistic regression analysis, factors that were independently associated with persistent hypertension were evaluated. Results Fifty four (27.7%) out of the total 195 women had persistent hypertension after puerperium. Serum creatinine and the age of the patient were the only factors associated with persistence of hypertension after puerperium. Conclusion Nearly every one in four mothers with pre-eclampsia/eclampsia are at risk of persistent hypertension after the puerperium. Serum creatinine, serum uric acid and participants' age were the only factors independently associated with persistence of hypertension after the puerperium.